Dinâmica espaço temporal e influência do metilmercúrio em peixes do Lago Janauacá, AM - França, Andressa de Jesus (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
Mercury is encountered in the Amazon rivers and lakes and can be derived from both natural and anthropogenic sources. This element is toxic for biota in any of its chemical forms. However, the organic form, methylmercury (MeHg), is considered the most toxic, bioaccumulates more easily and biomagnifies along the food chain. Many Amazonian fishes have elevated MeHg concentrations; however information on the effects of chronic mercury exposure is scarce. Therefore, the aim of this study was to evaluate the temporal and spatial dynamics of methylmercury concentrations in water and sediment, and its bioaccumulation and toxicological effects in fish of Janauaca Lake, Amazonas. Samples were collected at eight sites on the lake, located at different distances from the Solimões River, four in the northern part of the lake and four in the southern part. Water, sediments and limnological parameters were sampled at each site, during the low-water and high- water seasons. Fish were only collected at low water and included the species: Pterygoplichthys pardalis, Hoplias malabaricus and Cichla spp. Water, sediment and muscle tissue of fishes were analyzed for methylmercury. Fish were also assayed for biomarkers of genotoxic (frequency of micronucleus and erythrocyte nuclear abnormalities), histopathological (index of liver lesion) and biochemical effects (metallothionein concentration). Dissolved organic carbon was positively correlated with MeHg concentrations in water in both seasons, while dissolved oxygen, pH and electrical conductivity were negatively correlated with MeHg concentration in water only during the high-water season. The highest MeHg concentrations in water (0,68 a 1,21 ng/L) were observed in the southern part of the lake and in the hypolimnion at high-water. The MeHg concentrations in the sediment (0,20 a 0,56 μg/kg) were similar throughout the lake and slightly higher during the high-water season. While MeHg concentrations in P. pardalis (0,02±0,01 mg/kg) and in Cichla spp. (0,66±0,31 mg/kg) were similar at all sampling points, MeHg levels in H. malabaricus (0,66±0,29 mg/kg) were higher in the southern part of the lake,. Micronucleus were not observed and the frequency of erythrocyte nuclear abnormalities was low (0,07±0,17% e 0,26±0,19%, respectively) in both P. pardalis and in H. malabaricus (Cichla spp. was not evaluated). Metallothionein concentrations (2,50±0,90 μg/mg prot) and the index of hepatic lesion in H. malabaricus (22±4) were highest in the south part of the lake. The higher MeHg concentrations observed in water and H. malabaricus in the southern part of the lake indicated that the environmental conditions in this region are more conducive to methylation. The toxic effects observed with biomarkers may not have been caused exclusively by methylmercury. Other environmental stressor in the south region of the lake may also be involved. These results demonstrate that the dynamics and bioaccumulation of methylmercury can vary between regions in the same Amazonian lake, depending on proximity and connection to the river main channel, water type, depth, area and connection with upland and wetland environments.
Keywords: Mercúrio; Peixe de lago; Biomarcadores